Descriptive Findings on the Convergence of Female and Male Mortality in Europe - Juha Alho (The Research Institute of the Finnish Economy (ETLA), 2016)
Female life expectancy has almost universally been higher than male life expectancy. But, both have increased rapidly during the past century. European countries differ as regards the magnitude and time trends of the female-male difference. In countries that can be characterised as Egalitarian from the point of view of gender equality, the difference increased rapidly after World War II. It is thought that a major factor in this was then wider adoption of smoking on the part of males. Subsequently the gap has clearly narrowed, and it is believed that the narrowing continues. In countries that can be characterised as Traditional from the point of view of gender equality, the gap started to widen already a century ago, with acceleration after World War II. these countries show only limited evidence of subsequent narrowing. In former socialist countries the gap has been large, and shows little narrowing. These developments are described in detail by graphical displays. It is shown that considerable heterogeneity exists in the time trends within the three groups of European countries.
Keywords: 330; Female advantage; historical mortality data; life expectancy; mortality; survival probabilities